Surfing the web during pandemic flu: availability of World Health Organization recommendations on prevention - Ravà Lucilla; Rizzo Caterina; Pandolfi Elisabetta; Romano Mariateresa; Gesualdo Francesco; Lucente Daniela; Tozzi Alberto E (BMC, 2010)
Abstract Background People often search for information on influenza A(H1N1)v prevention on the web. The extent to which information found on the Internet is consistent with recommendations issued by the World Health Organization is unknown. Methods We conducted a search for "swine flu" accessing 3 of the most popular search engines through different proxy servers located in 4 English-speaking countries (Australia, Canada, UK, USA). We explored each site resulting from the searches, up to 4 clicks starting from the search engine page, analyzing availability of World Health Organization recommendations for swine flu prevention. Results Information on hand cleaning was reported on 79% of the 147 websites analyzed; staying home when sick was reported on 77.5% of the websites; disposing tissues after sneezing on 75.5% of the websites. Availability of other recommendations was lower. The probability of finding preventative recommendations consistent with World Health Organization varied by country, type of website, and search engine. Conclusions Despite media coverage on H1N1 influenza, relevant information for prevention is not easily found on the web. Strategies to improve information delivery to the general public through this channel should be improved.